SOME SHRUB AND TREE TAXA IN THE GRASSLAND-PASTURE AND NATURAL VEGETATION OF TURKEY - Başbağ, Mehmet; Çaçan, Erdal; Sayar, Mehmet Salih; Karan, Halil (Bilal GÜMÜŞ, 2017)
Some shrub and tree taxa identified by different researchers in the meadow-pasture and natural vegetation of Turkey have been summarized in paper. Total 108 genus and 227 taxa were identified from 49 plant families. Although the vast majority of these taxa (165 taxa-72.7%) had shrub formation and the numbers of taxa in tree formation was only 27 taxa (11.9%). The other 35 plant taxa (15.4%) had a transitional formation between shrub and tree formations. When plants were ordered in terms of family, genus and taxa; Rosaceae was the first number family in 14 genus and 38 taxa (16.7%), Leguminosae in 12 genus and 35 taxa (15.9%), and Labiatae family in 11 genus and 25 taxa (11.0%) followed it. Even though the most taxa possessing families for shrub formation were Leguminosae (36 taxa), Labiatae (25 taxa) and Rosacea (21 taxa), for tree formation the ranking was as Fagaceae (5 taxa), Anacardiaceae (3 taxa), Ericaceae, Cupressaceae and Moraceae (2 taxa). Fagaceae (5 taxa), Anacardiaceae (3 taxa), Ericaceae, Cupressaceae ve Moraceae (2 taxa) families respectively had the most taxa belonging to transitional formation between shrub and tree formations. The results showed that the Kermes oak (Quercus coccifera) (in 11 studies), Black shrub (Paliurus spina-christi) (in 9 studies) and Murt shrub (Myrtus communis) (in 7 studies) were the most cited and frequently encountered shrub taxa by researchers in Turkey. Additionally, among the taxa were identified seven taxa as "endemic" and five taxa as “rare”plants.
Keywords: Agricultural Engineering; Ziraat Mühendisliği